The feelings of diabetic pregnant women - Maria Gorete Andrade Bezerra; Francisca Ana Martins Carvalho; Tanara Távora Sobreira (Rev Rene)
The mellitos diabetes is a systemic disease characterized by the dismetabolism of carbohydrates. It can be similar in man and woman. During the pregnancy the woman com be attacked. We identied the feelings of diabetic pregnant, the complications of the disease towards the embryo. The study was done in amaternity in Fortaleza – Ceará –Brasil, with to pregnant during the months August to october of 1999. The interviews were recorded and ranked by types. We concluded that the pregnancy is a period of emotional crisis, herself insecure because of the ignorance about the disease and also concerning to the problems.